2003
DOI: 10.1183/09031936.03.00001903
|View full text |Cite
|
Sign up to set email alerts
|

Trends in asbestos body counts in bronchoalveolar lavage fluid over two decades

Abstract: Trends in asbestos body counts in bronchoalveolar lavage fluid over two decades. P. Dumortier, J. Thimpont, V. de Maertelaer, P. De Vuyst. #ERS Journals Ltd 2003. ABSTRACT: As in most western countries, the use of asbestos has decreased in Belgium since the mid 19709s. Successive regulations have lowered the permissible levels of exposure and prohibited the use of various asbestos products.In order to assess the impact of these prevention measures on the pulmonary fibre burden of asbestos-exposed patients, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
2
8
0
1
Order By: Relevance
“…Nevertheless, asbestos bodies were easily detectable in the lung dust analyses and histological evaluations (Figure 3a). This fact is confirmed by other authors [25][26][27] and in other studies [28]. Asbestos fibers, including chrysotile/white asbesbeen diagnosed as a bridge finding for BK 4104, recognition as an occupational disease had been recommended and this would not have been possible without the quite demanding lung dust analysis and histological examination applying iron staining.…”
Section: Discussionsupporting
confidence: 68%
“…Nevertheless, asbestos bodies were easily detectable in the lung dust analyses and histological evaluations (Figure 3a). This fact is confirmed by other authors [25][26][27] and in other studies [28]. Asbestos fibers, including chrysotile/white asbesbeen diagnosed as a bridge finding for BK 4104, recognition as an occupational disease had been recommended and this would not have been possible without the quite demanding lung dust analysis and histological examination applying iron staining.…”
Section: Discussionsupporting
confidence: 68%
“…We found that the slow decrease in AB in BAL that was observed in a similar study covering the latter part of the 20th century8 has been followed by a much faster decline in the 21st century.…”
Section: Introductionsupporting
confidence: 80%
“…This decrease is four times more pronounced than the trend from around 0.6 AB/mL in 1983 to around 0.4 AB/mL in 2000 reported by Dumortier et al ,8 also in Belgium. The acceleration in the decline of AB in BAL observed in our study, compared with the earlier study,8 presumably reflects the different phases in the decrease of asbestos usage in Belgium over the past decades, combined with changes in the types of work. Belgium was one of the top asbestos-consuming countries during the 1960s;23 asbestos usage started to decrease after the mid-1970s until finally (nearly) all use of asbestos was banned (1998).…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations